p16INK4a/Ki-67 co-expression specifically identifies transformed cells in the head and neck region - Prigge, Elena-Sophie; Tóth, Csaba; Dyckhoff, Gerhard; Freier, Kolja; Plinkert, Peter K.; Hoffmann, Jürgen; Vinokurova, Svetlana; Knebel Doeberitz, Magnus von; Reuschenbach, Miriam (International journal of cancer, 2015)
p16INK4a immunohistochemical overexpression is an overall reliable surrogate marker of human papillomavirus (HPV)-associated head and neck squamous cell carcinomas (HNSCC). However, cases of ambiguous p16INK4a overexpression are regularly detected in the head and neck: p16INK4a expression can be observed in non-malignant tissue, such as tonsillar crypt epithelium and a proportion of branchial cleft cysts. Additionally, diverse patterns of p16INK4 expression can complicate interpretation of “p16INK4a-positivity”. These aspects impede the unrestricted application of p16INK4a as a diagnostic marker in the head and neck. We hypothesized that combined detection of p16INK4a and the proliferation marker Ki-67 could support clarification of ambiguous p16INK4a expression in the head and neck by specifically indicating p16INK4a-expressing cells with proliferative activity. p16INK4a/Ki-67 co-expression in a combined staining procedure was correlated to distinct p16INK4a expression patterns and HPV status (HPV DNA followed by E6*I oncogene mRNA detection) in 147 HNSCC and 50 non-malignant head and neck samples. p16INK4a/Ki-67 co-expression only occurred in transformed cells of the head and neck. Co-expression was never detected in non-transformed cells. Combined p16INK4a/Ki-67 expression was stringently associated with a diffuse p16INK4a expression pattern. All HPV oncogene-expressing HNSCC showed p16INK4a/Ki-67 co-expression. We demonstrate that p16INK4a/Ki-67 co-expression occurs exclusively in transformed cells of the head and neck. Our findings indicate a substantial impact of combined p16INK4a/Ki-67 expression in the assessment of ambiguous p16INK4a expression in the head and neck by specifically identifying p16INK4a-expressing cells with proliferative activity. This property will be of considerable significance for head and neck histo- and cytopathology.
Im Titel ist „INK4a“ hochgestellt
Published online: 7 Aug 2014
Gesehen am 11.08.2017